The Tradition of Malam Pacar (WENNI MAPPACCI) In Sidenreng Rappang Regency, Timoreng Panua, Panca Rijang District - Nabila Rahmayuni Saharuddin; Abdul Rahman (International Journal of Social Service and Research, 2021)
The study aims to learn about one of the traditional bugis mappacci in Timoreng Panua, Panca Rijang district. The culture of each company is made up of both great and small elements that constitute a component of an integral union. Marriage is one of the most basic things that a human can experience in its phase. Marriage is a very sacred thing in the eyes of the people. Marriage is essentially a union between two separate families-the groom's and the bride's. (1) mammanu '-manu' (2) mappettuada, (3) mappasau botting & cemme passih, (4) mappacci (wenni mappacci), (5) mappanre temme, (6) madduppa botting, (8) mappasikarawa, (9) mapparola, and others. In this journal the author will discuss little about the procession of mappacci (wenni mappacci). Will be discussed on the meaning and procession of the mappacci